"She'll be right, mate!": do Australians take their health for granted? - Paul Scuffham; Andrew Wilson; Jennifer Whitty; Elizabeth Kendall; Asiyeh Salehi; Paul Harris (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONHealth consciousness highlights the readiness of individuals to undertake health actions and take responsibility for their health and the health of others. AIMTo examine the health consciousness of Australians and its association with health status, health-care utilisation and sociodemographic factors. METHODSThis quantitative cross-sectional study was a part of a larger project aiming to engage the general public in health-care decision-making. Adults from Queensland and South Australia (n=1529) were recruited to participate by a panel company. The questionnaire included the Health Consciousness Scale (HCS), health status, health-care utilisation, sociodemographic and socioeconomic variables. RESULTSThe health consciousness of Australians was relatively low (mean score=21), compared to other international administrations of the HCS, and further investigations revealed that more health-conscious people tended to live in South Australia, be female and single, experience poorer physical and mental health and were more frequent users of health-care services. DISCUSSIONThe general approach to health in this sample of the Australian public may reflect 'here and now' concerns. It appears that an attitude of 'she'll be right, mate' prevails until a change in an individual's health status or their exposure to the health system demands otherwise. These findings need to be investigated further to see if they are confirmed by others and to clarify the implications for primary health programmes in Australia in redressing the public's apparent apathy.